Phytochemical Evaluation and Antibacterial Activity of Espeletia Schultzii (Asteraceae) Inflorescences - De los Ríos, Carmen; Hidalgo Báez, Doris; Contreras, Quilianio; Crescente, Oscar; Caserta, Adela (Ciencia)
Â The increasing interest for the medicinal properties in plants is what induced the present work and was selected for the ethnobotanical information the species Espeletia schultzii Wedd. (Frailejón de Octubre), of the family Asteraceae, to accomplish an in vitro evaluation of its antibiotic and phototoxic activities. This species is used for the treatment of asthma in folk medicine in the Venezuelan Andes. A phytochemical evaluation was carried out which confirmed that the inflorescences extract contains kaurenic acids, it was isolated and identified benzophenone and two flavonoids, identified as quercetin and its 3-0-galactoside. These are the first flavonoids found in this species, and this is the first report of benzophenone in genus Espeletia. Three fractions obtained of the ethyl acetate extract, as well as the aqueous residual extract,were selected to accomplish an in vitro evaluation of their antibiotic and phototoxic activities. These activities were tested employing bacteria of clinical origin. Only one of the ethyl acetate fractions and the aqueous residual were found active against at least one bacterial strain. As far as we know, this study constitutes the first report on evaluation of the antibacterial activity of E. schultzii Wedd. Â